Knowledge and experience of women about dental services utilization during pregnancy: A cross-sectional questionnaire study - Kapu Swathi; Ramesh Kumar Koothati; Rashmitha Roy Motor; Priyadarshini; C H RajaShekar; Sunayana Vallakonda (Wolters Kluwer Medknow Publications, 2021)
Aim of the Study: The present study was aimed to assess the knowledge and experience of women about dental services utilization during pregnancy. Methodology: A hospital-based, cross-sectional questionnaire-based study was conducted among 300 women of age between 18 and 45 years who attended Malla Reddy Dental Hospital during 3 months period from October 2019 to December 2019. A questionnaire was distributed to all the participants who had given consent to participate in the study. Results: Only 30.7% of the participants attended for dental checkup during their pregnancy. Among them, most of the people (52%) had visited dentist for toothache, followed by gum care (29.34%) and regular checkup (18.47%). Most of the subjects (69.3%) did not use dental services as they were unaware of dental checkup during pregnancy. A significant difference was found between the urban and rural participants regarding the visit to the dentist during pregnancy (P = 0.000, Chi-square value = 19.157). Conclusion: Most of the women unaware of dental checkup during pregnancy. They were also not sure aware of dental treatments which can be done during pregnancy and consequences of poor oral hygiene on pregnancy outcome.